Who Would Gain Most from Efforts to reach the Millennium Development Goals for Health? An Inquiry into the Possibility of Progress that Fails to Reach the Poor - Gwatkin, Davidson R. (World Bank, Washington, DC, 2013)
This paper is an inquiry into the possibility of progress toward the Millennium Development Goals (MDGs) targets for health that does not significantly benefit the disadvantaged people whom the MDGs are intended to serve. The possibility arises because the MDGs health targets, unlike most other prominent MDGs targets, are stated in terms of improvement in societal averages rather than in terms of gains among poor groups within societies. Since improvements in any group, including the better-off, would produce improvements in societal averages, progress toward targets expressed in those terms does not necessarily reflect improvements in conditions among the poor. The inquiry begins by examining the implications of two alternative scenarios for progress toward the MDGs under-five mortality target: a "top-down" scenario, with gains highly concentrated among the better-off; and a converse, "bottom-up" scenario, under which gains flow primarily to the poor. The second part of the inquiry examines the plausibility the two scenarios. The conclusion is that, while the "pure" top-down scenario is unlikely, some approximation of it is considerably less improbable than a bottom-up scenario. The implication is that special efforts will be required to ensure that health and development initiatives reach poor people if they are to gain significantly from progress toward the MDGs health targets.